2004
DOI: 10.1128/mcb.24.12.5324-5331.2004
|View full text |Cite
|
Sign up to set email alerts
|

The TALE Homeodomain Protein Pbx2 Is Not Essential for Development and Long-Term Survival

Abstract: Pbx2 is one of four mammalian genes that encode closely related TALE homeodomain proteins, which serve as DNA binding partners for a subset of Hox transcription factors. The expression and contributions of Pbx2 to mammalian development remain undefined, in contrast to the essential roles recently established for family members Pbx1 and Pbx3. Here we report that Pbx2 is widely expressed during embryonic development, particularly in neural and epithelial tissues during late gestation. Despite wide Pbx2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 45 publications
1
98
1
Order By: Relevance
“…23,24 Deletion of TALE genes is also associated with impaired hematopoiesis. Both Meis1 and Pbx1 are essential for definitive hematopoiesis whereas Pbx2 is reported to be dispensable for normal hematopoiesis 25 and Pbx3 deficiency is associated with early death due to central respiratory failure. 26 We provide evidence that defined HOX/TALE gene expression signatures may have specific prognostic value and that targeting clinically relevant HOXA/PBX3 axes may provide therapeutic benefit to patients with CN-AML.…”
Section: Hoxa/pbx3 Knockdown Impairs Growth and Sensitizes Cytogenetimentioning
confidence: 99%
“…23,24 Deletion of TALE genes is also associated with impaired hematopoiesis. Both Meis1 and Pbx1 are essential for definitive hematopoiesis whereas Pbx2 is reported to be dispensable for normal hematopoiesis 25 and Pbx3 deficiency is associated with early death due to central respiratory failure. 26 We provide evidence that defined HOX/TALE gene expression signatures may have specific prognostic value and that targeting clinically relevant HOXA/PBX3 axes may provide therapeutic benefit to patients with CN-AML.…”
Section: Hoxa/pbx3 Knockdown Impairs Growth and Sensitizes Cytogenetimentioning
confidence: 99%
“…While the single Pbx2 knockout mice are viable and fertile , Pbx3 null mice are born, but die within a few hours owing to central respiratory failure . Importantly, Pbx2 partly compensates for Pbx1 (Capellini et al, 2006;Selleri et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pbx2* (pre B-cell leukemia transcription factor 2) ((-), see in the text) It has been found that Pbx2 -/-embryos are born at the expected Mendelian frequencies and exhibit no detectable abnormalities in development and organogenesis (Selleri, DiMartino et al 2004), however they show limb abnormalities (Capellini, Di Giacomo et al 2006). Supporting its role in this phenomenon, its elevated expression in limb buds after RA treatment has been demonstrated.…”
Section: Meis1 and Meis2* (Myeloid Ecotropic Viral Integration Site) (↑)mentioning
confidence: 82%